OPTIMAL CHOICE IN SURGERY FOR NECROTIC PARAPROCTITIS - Karabayev J.A., (Research Focus International Scientific Journal, 2024)
The article discusses the results of treatment in 254 patients operated on in the proctology department of the multidisciplinary clinic of the Samara State Medical University in the period 2016-2022, among which patients with necrotic forms of the disease accounted for 31 (12.2%) patients. Among them, 236 (92.9%) had an aerobic etiology of damage to the perirectal tissue. The mean age of the patients was 62.1±3.9 years.